Asymmetric Aldol Reaction of Dichloroacetaldehyde Catalyzed by Diarylprolinol. Issue 14 (2nd June 2016) - Hayashi, Yujiro; Nakamura, Daichi; Yasui, Yusuke; Iwasaki, Kotaro; Chiba, Hiroaki
Abstract: The asymmetric cross‐aldol reaction of dichloroacetaldehyde with aldehyde pronucleophiles proceeds in the presence of a trifluoromethyl‐substituted diarylprolinol to afford γ, γ‐dichloro‐β‐hydroxy aldehydes in good yield with excellent enantioselectivity. The obtained products are useful synthetic intermediates; they were successfully converted to form chiral alkynes and dichloroalkenes. Abstract :